Assessment of tourists perceived without travel risks and intention to visit night market aftermath the COVID-19 pandemic: An empirical approach - Wang, Lei; Zhang, Qi; Wong, Philip Pong Weng* (University of Lodz, 2022)
Prior studies on night market tourism have mainly investigated by governments and scholars on the current situation products and development strategies with descriptive research. There are no empirical studies that have explored the perceptions of tourists in the development of night market tourism. More importantly, because of the COVID-19 pandemic, issues of night market products and services, and tourists’ opinions about night markets have become a challenge. This study aims to examine the relationships between attitude, subjective norm (SN), perceived behavioural control (PBC), perceived without travel risk, and visit intention towards night markets aftermath of the COVID-19 pandemic. A quantitative approach was used using an online survey method involving 387 respondents followed by subsequent empirical testing of the proposed hypotheses, which was performed using SPSS and AMOS. The results indicate that attitude, SN, PBC, and perceived without travel risk positively influence intention. Furthermore, SN also displayed a significant positive influence on attitude, PBC, and perceived without travel risk. Finally, the theoretical and practical implications, as well as limitations were discussed.